The Economic Crisis Seen from Israel: Cause and Effect - Lily Polliack (Nordicum-Mediterraneum, 2010)
The paper indicates a correlation between the economic crisis and America's Middle East policy. It contends that the protracted war effort in Iraq and Afghanistan have crippled the US national economy to a degree that only if the US changes its approach to Middle East conflict, will it be able to reduce the federal budget deficit, a necessary step towards economic recovery.